Sikap Siswa Terhadap Pembelajaran Berbasis Online dilihat dari Berbagai Variabel - Ariyani Cahyani; Ni Made Novi Suryanti; Sukardi Sukardi (Journal of Education and Teaching (JET), 2022)
Changes that occur in the learning process due to the COVID-19 pandemic. Therefore, the purpose of this study was to determine students' perceptions regarding the adaptation of online learning. This study uses a survey method with variables of gender, age and class. The research subjects were all students of social studies class at SMA Negeri 1 Gunungsari. Data was collected using a questionnaire with the help of google form. Data analysis was performed using descriptive and comparative statistics. The results showed that there were differences in student attitudes towards online-based learning during the COVID-19 pandemic from various variables. Female students aged 16 years and class X have a better perception of online-based learning. The implication is that online-based learning needs to pay attention to differences in gender, age and class variables in its implementation.